Pharmacophore-inspired discovery of FLT3 inhibitor from kimchi. (1st November 2021) - Zhu, Wen Jing; Lin, Li Ping; Liu, Dan; Qian, Jia Cheng; Zhou, Bei Bei; Yuan, Dan Dan; Tan, Ren Xiang
Highlights: Characterizes the "kimchi indoles" which were overlooked prior to this work. Identifies LTr1 (a major kimchi indole) as an inhibitor of FLT3, a kinase involved in acute myeloid leukemia (AML). Addresses the antitumor mechanism of LTr1, which lies in its inhibition on the FLT3 phosphoration and its downstream protein expressions. Ascertains the in vivo efficacy of LTr1 and its synergy with sorafenib (an anti-AML agent in clinic) in tumored mice. Abstract: Globally consumed kimchi is manufactured through fermenting cruciferous vegetables containing indole glucosinolates (IG). But few reports describe the IG metabolism during the fermentation. Here, we show that indole-3-carbinol (I3C), a breakdown product of IG, is transformed during the kimchi fermentation into 3, 3′-diindolylmethane (DIM) and 2-(indol-3-ylmethyl)-3, 3′-diindolylmethane (LTr1). LTr1 was found to kill the acute myeloid leukemia (AML) cells with FMS-like tyrosine kinase 3 (FLT3) receptor mutations, by inhibiting the FLT3 phosphorylation and the expression of downstream proteins (STAT5, ERK, and AKT). In the immune-depleted mice xenografted with human MV4-11 cells, LTr1 was demonstrated to reduce the tumor growth and synergize with sorafenib, an anti-AML agent in clinic. The work updates the chemical and biological knowledge about kimchi, and in particular establishes LTr1 as an FLT3 inhibitor that is effective and synergistic with sorafenib in treating AML.